Implementation of the Friday Recitation and Islamic Reflection Program in Strengthening Students' Moral Education at MI Raudlatul Hasan Maron Kulon - Izzul Haqqi; Ainur Rofiq Sofa (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2026)
This study aims to describe the implementation of the Friday Qur’anic Recitation and Islamic Reflection Program (JUMARI) in strengthening students’ moral education at MI Raudlatul Hasan Maron Kulon. The JUMARI program is designed as a routine religious habituation activity conducted every Friday through Qur’an recitation, collective prayers, and reflection on Islamic values. This study employed a qualitative approach with a case study design. Data were collected through observations of JUMARI activities, interviews with the head of the madrasah, teachers, and students, as well as program documentation. The findings indicate that the implementation of the JUMARI program contributes positively to the development of students’ moral character, as reflected in improved discipline, respect for teachers, regular prayer practices, and polite behavior in daily life. Moreover, the program strengthens the internalization of akhlaq al-karimah values through consistent habituation and teachers’ role modeling. Therefore, the JUMARI program is effective as a strategy for strengthening moral education among students at the madrasah ibtidaiyah level.